2021
DOI: 10.1002/lom3.10418
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive fluorescent assay for measuring carbon‐phosphorus lyase activity in aquatic systems

Abstract: In the oligotrophic ocean where inorganic phosphate (P i ) concentrations are low, microorganisms supplement their nutrient requirements with phosphorus (P) extracted from dissolved organic matter (DOM). Most P in DOM is bound as phosphate esters, which are hydrolyzed by phosphoesterases to P i . However, a large fraction of DOM-P occurs as phosphonates, reduced organophosphorus compounds with a C P bond that do not yield P i through simple ester hydrolysis alone. Phosphonates require an additional step that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…CLA was slightly elevated in the surface (114.0 ± 0.9 pmol P L -1 d -1 ) and decreased to a broad minimum in the subsurface around 100 meters (105.5 ± 0.6 pmol P L -1 d -1 ). These rates are low, but consistent with previously measured rates of CLA in the NPSG (6.1-931.0 pmol P L -1 d -1 ; Granzow et al, 2021). The high-resolution sampling around the DMC conducted on the PARAGON I expedition showed that CLA was highly variable in that region.…”
Section: Organic Phosphorus Remineralizationsupporting
confidence: 89%
See 4 more Smart Citations
“…CLA was slightly elevated in the surface (114.0 ± 0.9 pmol P L -1 d -1 ) and decreased to a broad minimum in the subsurface around 100 meters (105.5 ± 0.6 pmol P L -1 d -1 ). These rates are low, but consistent with previously measured rates of CLA in the NPSG (6.1-931.0 pmol P L -1 d -1 ; Granzow et al, 2021). The high-resolution sampling around the DMC conducted on the PARAGON I expedition showed that CLA was highly variable in that region.…”
Section: Organic Phosphorus Remineralizationsupporting
confidence: 89%
“…Several studies have found CLA to be somewhat independent of Pi concentration and have suggested that C-P lyase may be utilized as a mechanism for extracting labile C and N from organic matter (Benitez-Nelson et al, 2004;Chin et al, 2018). These conclusions are supported by the high CLA rates observed in seawater collected from the mesopelagic, although it is unclear what effects pressure and temperature modulation during incubation have on those results (Granzow et al, 2021). Recently, a phosphate insensitive cosmopolitan phosphomonoesterase produced by Bacteroidetes was found to be associated with phytoplankton and POM and was hypothesized to be used in C acquisition from phosphorylated compounds (Lidbury et al, 2022).…”
Section: Organic Phosphorus Remineralizationmentioning
confidence: 95%
See 3 more Smart Citations